Convert the following equation into standard form. \( \begin{array}{c}2 y=-4 x-9 \\ {[?] x+\square} \\ y=-9\end{array} \)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To convert the equation \(2y = -4x - 9\) into standard form, we first want it to look like \(Ax + By = C\). Step 1: Rewrite the equation. Divide both sides by 2, giving \(y = -2x - \frac{9}{2}\). Step 2: Rearranging gives us \(2x + y = -\frac{9}{2}\). Step 3: To eliminate the fraction, we can multiply the entire equation by 2: \(4x + 2y = -9\). Now we have it in standard form: \(4x + 2y = -9\). Now, substituting \(y = -9\) into the equation gives us an important point: if \(y\) is always -9, the value of \(x\) can be found by plugging -9 into the rearranged equation \(2x + (-9) = -\frac{9}{2}\), leading to all the interesting coordinate pairs along that line.